Nasal papilloma: A comparison between inverted papilloma and oncocytic schneiderian papilloma (Bangladesh Journal of Otorhinolaryngology, 2012)
The Schneiderian membrane gives rise to 3 morphologically distinct tumours: septal, inverted (IP) and oncocytic schneiderian papillomas (OSP). OSP, although, almost parallel to IP, still have its own distinct features in the incidence, location, clinical presentation and histological examination. Despite the differences, the standard treatment is still surgical removal of the tumour. External approach is preferred but in view of advanced endoscopic technique, it is feasible to remove the tumour endoscopically with carefully selected tumour presentation. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12033 Bangladesh J Otorhinolaryngol 2012; 18(2): 215-218